2022
DOI: 10.3390/ijerph191710576
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychosocial Factors in Brazilian Dentists Facing Risk of SARS-CoV-2 Infection in the Public and Private Sectors

Abstract: Dentists are at high risk of SARS-CoV-2 infection due to their close proximity to patients. Thus, the fear of contamination or spreading the virus to family members, coupled with financial need, can lead professionals to experience significant overload and psychological suffering. We investigated the perceptions of dental professionals in the public and private sectors regarding fear and anxiety related to patient care and the risk of infection in the face of the COVID-19 pandemic. Based on the previous litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results of this study add a new perspective to the literature and the reality of dental practice, since the COVID-19 pandemic has brought a new scenario to the job market and to health research. Recent studies have shown that the quality of life of dental professionals has been more greatly impacted, such as through a fear of becoming infected and dying from SARS-CoV-2 [16,17]. However, our study adds the perception of the pandemic in the presence of burnout syndrome, considered a limiting syndrome with a high prevalence among health professionals, and Brazil was considered the country with the second highest number of affected professionals according to the WHO [18].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The results of this study add a new perspective to the literature and the reality of dental practice, since the COVID-19 pandemic has brought a new scenario to the job market and to health research. Recent studies have shown that the quality of life of dental professionals has been more greatly impacted, such as through a fear of becoming infected and dying from SARS-CoV-2 [16,17]. However, our study adds the perception of the pandemic in the presence of burnout syndrome, considered a limiting syndrome with a high prevalence among health professionals, and Brazil was considered the country with the second highest number of affected professionals according to the WHO [18].…”
Section: Discussionmentioning
confidence: 85%
“…This relationship was also demonstrated by Antoniadou (2022) [19], who found that dentists between the ages of 25 and 35 showed greater burnout during the COVID-19 pandemic, mainly due to the challenges of the job market [19]. In our sample, the lower exposure in older dentists can be explained by the time of data collection, which corresponded to the first wave of the pandemic, when Brazil had a high prevalence of COVID-19, especially in older people, and at that time, there were still no vaccines, so the fear of dying from the infection in the workplace generated anguish and anxiety, thus over-riding financial factors, leading these professionals to cancel appointments [16].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Dos profissionais que participaram da pesquisa 63,9% relataram tinham o conhecimento protetor necessário para evitar a contaminação. Vale ressaltar que os dentistas que atendiam no setor público tinham mais medo de serem infectados quando comparados com aqueles que atuavam apenas em consultórios e clínicas privadas (3,11,20). Silveira et al, (2021) acreditam que os profissionais de saúde estão expostos diariamente a riscos que os tornam vulneráveis à infecção pelo novo coronavírus.…”
Section: Discussionunclassified
“…Sendo definida como um conjunto de ações voltada para a prevenção, minimização ou eliminação de riscos inerentes às atividades de pesquisa, ensino, produção, desenvolvimento tecnológico e principalmente prestação de serviços que é escopo dessa pesquisa. Esses riscos podem comprometer a saúde do homem e meio ambiente, afetando a qualidade de vida no trabalho (2,3). Na odontologia, biossegurança constitui-se em um conjunto de medidas de controle dos riscos ocupacionais, princípios de controle da infecção e práticas ergonômicas que buscam garantir que a assistência à saúde bucal aconteça sob condições adequadas de segurança para o profissional, o paciente e o ambiente (4,10).…”
Section: Introductionunclassified